The Corona Crisis - is this the time for Helicopter Money? - Marc C. Adam (Forum for a New Economy, 2020)
This paper first describes the basic idea of Helicopter Money and the context in which it evolved from Milton Friedman's famous 1969 essay until today. We discuss the challenges facing advanced economies, to which Helicopter Money has been proclaimed a possible solution. The paper provides a review of the recent debate around Helicopter Money and discusses the effectiveness of this tool in the current and future crises.
Keywords: B2; E4; E5; E6; H6; 330; Helicopter Money; central bank; fiscal policy